Physicochemical Properties of Collagen Extracted from Skin and Scale of Gaint Gouramy (Osphronemus guramy) and Proliferative Response of Human Dermal Fibroblast cell Culture to the Extracted Collagen - Tidarat Maleeratmongkon (Chulalongkorn University, 2014)
Thesis (M.Sc.)--Chulalongkorn University, 2006